Frequency and Severity of Symptoms of Premenstrual Syndrome in Reproductive Age Women Presented to Mardan Medical Complex - Hera, Komal; Amin, Nuzhat; Shehzadi, Shafaq; Alamzeb, Hina (Indus Journal of Bioscience Research, 2025)
Background: Premenstrual syndrome is a cyclical disorder characterized by physical, psychological, and behavioral symptoms occurring during the luteal phase of the menstrual cycle and resolving with menstruation. It affects social functioning, interpersonal relationships, and academic or occupational performance. The frequency and severity of symptoms differ across populations due to hormonal variations, lifestyle factors, and cultural perceptions. Data from Mardan are limited, where differences in socioeconomic status and healthcare access may influence reporting and recognition. Objective: To determine the frequency and severity of symptoms in patients of reproductive age with premenstrual syndrome presented to Mardan Medical Complex, Mardan. Study Design: Cross-sectional study. Duration and Place of Study: This study was conducted from December 2024 to May 2025 in the Department of Obstetrics and Gynecology at Mardan Medical Complex, Mardan. Methodology: A total of 151 women aged 18 to 48 years with regular menstrual cycles were included by non-probability consecutive sampling. Women with pregnancy, lactation, psychiatric illness, or use of hormonal or psychopharmacological therapy were excluded. Premenstrual syndrome was diagnosed when at least three recognized symptoms were present in the luteal phase. Severity was graded using the Premenstrual Symptoms Screening Tool. Results: The prevalence of premenstrual syndrome was 39.7%. Of these, 21.7% reported mild, 51.7% moderate, and 26.7% severe symptoms. Younger age (p<0.001), unmarried status (p<0.001), and lower body mass index (p<0.001) showed significant association, whereas socioeconomic, educational, and residential factors were not significant. Conclusion: Premenstrual syndrome is common in reproductive age women of Mardan, predominantly of moderate severity, and is associated with younger age, unmarried status, and lower body mass index.